Pendekatan Dalam Pengembangan Telaah Kurikulum Merdeka (PAI) - Amelia Amelia; Insanul Mizan; Jesika Mutiara; Rani Nurfitri; Mustafiyanti Mustafiyanti (Jurnal Budi Pekerti Agama Islam, 2024)
Curriculum is something tha is very important in education. As time goes by, the curriculum also needs to be developed. In developing a curriculum, there are approaches that need to be consideren, including academic, humanistic, technological and social reconstruction subject approaches. This article was written using reading material related to what was discussed through books and internet sources.